003 Gap junctional uncoupling with carbenoxolone slows conduction and increases vulnerability to ventricular arrhythmias in structurally normal hearts: an optical mapping study. (22nd September 2015) - Ng, F S; Lyon, A R; Shadi, I T; Chang, E T Y; Chowdhury, R A; Dupont, E; Peters, N S
Abstract : Background: Gap junctional uncoupling is thought to contribute to arrhythmogenesis through its effects on conduction slowing and creation of heterogeneities, often in the context of action potential or structural abnormalities. However, it is uncertain as to whether moderate conduction slowing through gap junctional uncoupling on its own, in the absence of action potential or structural changes, is sufficient to be pro-arrhythmic. We used optical mapping: (1) to study the effects of carbenoxolone, a gap junction uncoupler, on conduction velocity and action potential duration, and (2) to assess the effects of moderate conduction slowing and gap junctional uncoupling on arrhythmia vulnerability in structurally normal hearts. Methods: Normal rat hearts (n=12) were isolated and perfused with Krebs-Henseleit solution, then loaded with a voltage-sensitive dye (RH237) and perfused with an excitation-contraction uncoupler (10 μM blebbistatin) to eliminate motion artefact. Transmembrane voltage (Vm ) transients were recorded using a 256-photodiode array and epicardial activation was mapped across the anterolateral left ventricle during ventricular pacing (stimulus 1 mA, cycle length 180 ms). Hearts were then perfused with 30 μM carbenoxolone (CBX; n=6) or control (n=6) for 30 min and epicardial activation mapped every 2 min. Subsequently, hearts were subjected to programmed ventricular stimulation with up to three extrastimuli and assigned an Inducibility Quotient depending on ease of arrhythmia inducibility. Results: Carbenoxolone significantly slowed conduction across the left ventricular epicardial surface (Conduction velocity index: Baseline 100%, CBX 70% ± 2%, p<0.01) whereas there was no change in conduction velocity in control hearts after 30 min (Baseline 100%, Controls 98%±3%, p=NS). Carbenoxolone did not affect action potential duration (Baseline: APD50: 52±2 ms, APD75: 70±3 ms, APD90: 90±3 ms; CBX: APD50: 54±4 ms; APD75: 74±6 ms; APD90: 94±5 ms; all p=NS). Inducibility of ventricular arrhythmias was significantly increased in CBX hearts compared with control hearts during programmed stimulation (Inducibility quotient: CBX: 5.0±1.0; Control: 2.5±1.0; p<0.05). Conclusions: Gap junctional uncoupling with carbenoxolone produced a 30% reduction in conduction velocity without changes in action potential duration, and resulted in increased arrhythmia vulnerability in structurally normal hearts. These results suggest that moderate conduction slowing produced by gap junctional uncoupling in isolation, that is, in the absence of changes in action potential duration or structural abnormalities, is sufficient to increase susceptibility to ventricular arrhythmias, and therefore highlight the importance of gap junctional uncoupling in ventricular arrhythmogenesis.